Developing Guidelines and Competencies for the Training of Psychedelic Therapists. (September 2017) - Phelps, Janis
Research since the 1950s has shown that psychedelic-assisted psychotherapy has had significant positive effects in reductions of specific clinical symptoms and increases in quality of life as measured on a variety of indices. The intensity of focus on evidence-based outcomes, however, has resulted in a paucity of active discussions and research on the core competencies of the therapists themselves. The context of the history of psychedelic research reveals how this neglect of therapist variables occurred. With current discussions of Phase 3 and expanded access research programs for psilocybin-assisted and MDMA-assisted psychotherapies, there will be a great need for competent therapists trained in this clinical specialty. This is particularly the case if less restricted, legal medical use is approved within the next 6 to 10 years. This article is the first review and compilation of psychedelic therapist competencies derived from the psychedelic literature. These six therapist competencies are empathetic abiding presence; trust enhancement; spiritual intelligence; knowledge of the physical and psychological effects of psychedelics; therapist self-awareness and ethical integrity; and proficiency in complementary techniques. A further contribution of this review is a delineation of the 12 fundamental curricular domains of study for the training and development of these therapist competencies. As current legal restrictions evolve, aspects of these training guidelines will develop accordingly.